EVALUATION OF THE EFFECTIVENESS OF THE DRUG DISTREPTAZA IN THE PREVENTION OF ADHESIONS IN WOMEN WHO HAVE UNDERGONE ENDOSURGICAL OPERATIONS ON THE APPENDAGES OF THE UTERUS - Burxonova , S.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Adhesive processes in the pelvis are one of the most frequent complications after endosurgical operations on the appendages of the uterus. The aim of the study is to the evaluation of the effectiveness of the drug Distreptaza® in the prevention of adhesions in women after endosurgical operations on the appendages of the uterus. Materials. A total of 100 women were studied, 40 of them after fallopian tube surgery and 40 after cystectomy surgery. In the postoperative period, all women were treated with the drug Distreptaza®. The effectiveness of treatment was evaluated based on the analysis of ultrasound results and hysterosalpingography data. Results. As a result of the study, it was found that the use of Distreptaza® in women who underwent endosurgical operations on the appendages of the uterus reduces the likelihood of adhesions by 2.1 times. This indicates the effectiveness of this drug in the prevention of adhesions in women who have undergone endosurgical operations on the appendages of the uterus. Conclusion. Our studies have shown the high effectiveness of the drug Distreptaza® in the prevention of adhesions in women who have undergone endosurgical operations on the appendages of the uterus. The use of Distreptaza® in women who have undergone endosurgical operations on the appendages of the uterus reduces the likelihood of adhesions by 2.1 times.